Leveraging robust CNN architectures for real-time object recognition from conveyor belt - Moon, Nowrin Tasnim; Siddiqua, Sabiha Afrin; Parvin, Shahana; Muntaha, Sidratul; Hassan, K.M. Mehedi (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.